DEVELOPMENT OF INSTRUCTIONAL MEDIA â€œGAME MATH COMIC STORYâ€ BASED ANDROID ON NUMBER - Sulistio, Wahyu; Qohar, Abd (Journal of Education Research and Evaluation, 2020)
This research was conducted with the purpose to produce mathematics instructional media based game and comic stories for android. This study aimed at assisting students in studying number material and increasing reading interest for 7th grade students. Media developed were stories that were made into an adventure game made with "appsgeyser.com". The research method was research and development. The development of this medium used 4D (Four-D) development techniques consisting of Define, Design, Develop, and Disseminate stages. To obtain quality media, validation and experiment were done. The result of this study indicated that mathematics instructional media comic game story based android could improve the positive nature and spirit of students in learning. The validity value of media was 3.2 and the practical value of media was 3.14